Daniel X : the manga. 2 - Patterson, James, 1947-; Kye, Sŭng-hŭi (Patterson, James, 1947- Daniel X novels., 2011)
In the sleepy town of Holliswood, a twisted alien TV producer is using his powers to throw the town into chaos--and documenting every minute of it. Fresh from his victory over Number 6, Daniel X is the only one who can stop this made-for-TV tyrant, but the devilish director has other plans. He wants to film the most spectacular finale the world has ever seen, starring Daniel himself!